Effect of amount and time of potassium application on herbage yield, oil yield, oil content and quality of lemongrass (Cymbopogon flexuosus) under semi arid tropical conditions - H P Singh, M Singh, N Guleria, (Journal of Spices and Aromatic Crops, 2014)
A field experiment on lemongrass (Cymbopogon flexuosus) comprising 12 treatments of four levels of K2O (0, 40, 80 and 120 kg ha 1 year-1) and three time of applications (Full basal at the time of planting, ½ basal + ½ after six months and 1/3rd basal +1/3rd after six months and 1/3rd after first harvest) were tested during 2006–2008. Results showed that application of 40 kg K2O ha 1 year-1 in three splits i.e. 1/3rd basal +1/3rd after six months and 1/3rd after first harvest produced maximum herbage and oil yield which was at par with 80 kg K2O ha 1 year-1 applied as a basal.